A contrastive analysis of rhetorical patterns in English and Spanish expository journal writing: a study for contrastive rhetoricians, teachers of second language composition, and translators - Moreno, Hilda (Colombian Applied Linguistics Journal, 2013)
Blackwell (2001) summarizes that A contrastive analysis of rhetorical patterns in English and Spanish expository journal writing analyzes “writing samples from contemporary magazines generally considered by native speakers to contain ‘good writing’” (as cited in Sanchez-Escobar, 2012, pp. 5-10). In addition, Blackwell (2001) mentions that this book “should be required reading for all of us who write in a second language and who try to teach others to do the same” (p. 9).